Economic analysis of remote monitoring in patients with implantable cardioverter defibrillators or cardiac resynchronization therapy defibrillators in the Trento area, Italy - Marini, Massimiliano; Videsott, Lodovica; Dalle Fratte, Chiara Francesca; Francesconi, Andrea; Bonvicini, Eleonora; Quintarelli, Silvia; Martin, Marta; Guarracini, Fabrizio; Coser, Alessio; Benetollo, Pier Paolo; Bonmassari, Roberto; Boriani, Giuseppe (Frontiers in Cardiovascular Medicine, 2023)
Introduction Remote monitoring (RM) technologies have the potential to improve patient care by increasing compliance, providing early indications of heart failure (HF), and potentially allowing for therapy optimization to prevent HF admissions. The aim of this retrospective study was to assess the clinical and economic consequences of RM vs. standard monitoring (SM) through in-office cardiology visits, in patients carrying a cardiac implantable electronic device (CIED). Methods Clinical and resource consumption data were extracted from the Electrophysiology Registry of the Trento Cardiology Unit, which has been systemically collecting patient information from January 2011 to February 2022. From a clinical standpoint, survival analysis was conducted, and incidence of cardiovascular (CV) related hospitalizations was measured. From an economic standpoint, direct costs of RM and SM were collected to compare the cost per treated patient over a 2-year time horizon. Propensity score matching (PSM) was used to reduce the effect of confounding biases and the unbalance of patient characteristics at baseline. Results In the enrollment period, N = 402 CIED patients met the inclusion criteria and were included in the analysis (N = 189 patients followed through SM; N = 213 patients followed through RM). After PSM, comparison was limited to N = 191 patients in each arm. After 2-years follow-up since CIED implantation, mortality rate for any cause was 1.6% in the RM group and 19.9% in the SM group (log-rank test, p < 0.0001). Also, a lower proportion of patients in the RM group (25.1%) were hospitalized for CV-related reasons, compared to the SM group (51.3%; p < 0.0001, two-sample test for proportions). Overall, the implementation of the RM program in the Trento territory was cost-saving in both payer and hospital perspectives. The investment required to fund RM (a fee for service in the payer perspective, and staffing costs for hospitals), was more than offset by the lower rate of hospitalizations for CV-related disease. RM adoption generated savings of −€4,771 and −€6,752 per patient in 2 years, in the payer and hospital perspective, respectively. Conclusion RM of patients carrying CIED improves short-term (2-years) morbidity and mortality risks, compared to SM and reduces direct management costs for both hospitals and healthcare services.